일본의 의료정보 활용 관련 법제도에 관한 연구 - 김상태(SangTae Kim) (생명, 윤리와 정책, 2022)
일본은 2015년 민감한 개인정보를 보호하기 위해 개인정보호법을 개정하여 “배려를 요하는 개인정보”를 신설하였고 의료정보는 이러한 배려를 요하는 개인정보에 해당되었다. 그런데 배려를 요하는 개인정보를 제3자에게 제공하기 위해서는 법률에서 규정하는 등 예외적인 경우를 제외하고는 본인의 동의가 있어야 했기 때문에, 연구기관 등이 배려를 요하는 개인정보를 적극적으로 활용하기에는 어려움이 있었다. 이에 일본은 개인정보보호법하에서의 의료정보 활용의 한계를 극복하고 적극적으로 의료정보를 활용하기 위해 차세대의료기반법을 제정하였다. 차세대의료기반법은 환자 본인 또는 그 유족이 정보제공에 대한 동의를 거부하지 않는 한 환자의 정보를 활용할 수 있는 Opt-out 절차를 채택하여 의료정보 활용의 가능성을 높였다. 즉, 의료정보취급사업자(병원, 약국 등)는 본인 또는 그 유족이 거부의 의사표시를 하지 않는 한 의료정보를 익명가공의료정보작성사업자에게 제공할 수 있고, 익명가공의료정보작성사업자는 의료분야의 연구개발을 위하여 의료정보를 익명가공의료정보로 가공한 후 익명가공의료정보취급사업자(의료기관, 연구자 등)에게 제공할 수 있게 되었다. 따라서 차세대의료기반법은 익명화를 통해 개인의 정보를 보호하면서 의료정보의 활용성을 높인 법률이라고 할 수 있다. The Japanese government has amended the Personal Information Protection Act to add and establish a new category of special care-required personal information to protect personal information. Medical information fell under such rubric. However, to provide it to a third person, the consent of the principal of the information was required, except for exceptional cases. Therefore, difficulties were experienced in using such information. For this reason, the Japanese government enacted the Commentary on Next Generation Medical Infrastructure Law, as a special law of the Personal Information Protection Act, to utilize medical information actively. The Commentary on Next Generation Medical Infrastructure Law increases the possibility of using medical information by adopting an opt-out procedure that allows its use, unless the principal of the information refuses to consent to its provision. That is, business operators handling medical information (hospitals, pharmacies, etc.) can provide medical information to business operators who produce anonymized medical information, unless the principal of the information refuses to provide it. The business operators who produce anonymized medical information can anonymize such information for R&D purposes and provide it to other business operators (medical institutions, researchers, etc.) who handle such anonymized medical information. KCI Citation Count: 5